2014
DOI: 10.1371/journal.pone.0101575
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Na+/H+-Antiporter NhaA from Salmonella Typhimurium

Abstract: Na+/H+ antiporters are integral membrane proteins that are present in almost every cell and in every kingdom of life. They are essential for the regulation of intracellular pH-value, Na+-concentration and cell volume. These secondary active transporters exchange sodium ions against protons via an alternating access mechanism, which is not understood in full detail. Na+/H+ antiporters show distinct species-specific transport characteristics and regulatory properties that correlate with respective physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
5
18
0
Order By: Relevance
“…This gave rise to negative transient currents of up to 5 nA in amplitude (Fig. 1B) with similar characteristics to those previously reported for EcNhaA [6,20] and StNhaA [12]. The negative polarity of these currents is in accordance to the overall transport of one negative charge per transport cycle to the interior of the liposomes.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This gave rise to negative transient currents of up to 5 nA in amplitude (Fig. 1B) with similar characteristics to those previously reported for EcNhaA [6,20] and StNhaA [12]. The negative polarity of these currents is in accordance to the overall transport of one negative charge per transport cycle to the interior of the liposomes.…”
Section: Resultssupporting
confidence: 87%
“…1C and D), yielding the same K D Na value as for EcNhaA and a pK value which is shifted by less than one pH unit into the acidic. For comparison we also fitted data obtained previously for StNhaA to the kinetic model [12] and included the obtained kinetic parameters together with those from EcNhaA in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar cation transporters have been found in other bacteria, including human pathogens [30]. Activity of these, mostly high-yield anti-porters, locally enrich the microenvironment with ions; thus a discrete ionic zone formed on the bacterial surface creates a distinct environment that differs from the surrounding soil or water.…”
Section: Resultsmentioning
confidence: 64%
“…Further electrophysiological investigation of a number of enterobacterial CPA2 NhaA Na + /H + exchangers yielded similar results as for EcNhaA: bell-shaped pH profiles at symmetrical pH and acidic down-regulation by substrate competition as predicted by the simple kinetic model (Calinescu et al, 2014a, Lentes et al, 2014. It should also be mentioned here that we could prove (Calinescu et al, 2014a) that the previously reported "pH-independent" behavior of the NhaA exchanger from Helicobacter pylori was just a result of the investigation method and the experimental conditions used.…”
Section: Experimental Validation Of the Kinetic Modelmentioning
confidence: 63%